The rationale behind grafting haploidentical hematopoietic stem cells - Richard T. Maziarz; Rachel J. Cook (Hematology)
The ability to perform hematopoietic cell transplant across major histocompatibility complex barriers can dramatically increase the availability of donors and allow more patients across the world to pursue curative transplant procedures for underlying hematologic disorders. Early attempts at haploidentical transplantation using broadly reactive T-cell depletion approaches were compromised by graft rejection, graft-versus-host disease and prolonged immune deficiency. The evolution of haploidentical transplantation focused on expanding transplanted hematopoietic progenitors as well as using less broadly reactive T-cell depletion. Significant outcome improvements were identified with technology advances allowing selective depletion of donor allospecific T cells, initially ex-vivo with evolution to its current in-vivo approach with the infusion of the highly immunosuppressive chemotherapy agent, cyclophosphamide after transplantation procedure. Current approaches are facile and portable, allowing expansion of allogeneic hematopoietic cell transplantation for patients across the world, including previously underserved populations.